2016
DOI: 10.1038/modpathol.2016.98
|View full text |Cite
|
Sign up to set email alerts
|

The oncocytic subtype is genetically distinct from other pancreatic intraductal papillary mucinous neoplasm subtypes

Abstract: In 2010, the World Health Organization reclassified the entity originally described as intraductal oncocytic papillary neoplasm as the ‘oncocytic subtype’ of intraductal papillary mucinous neoplasm. Although several key molecular alterations of other intraductal papillary mucinous neoplasm subtypes have been discovered, including common mutations in KRAS, GNAS, and RNF3, those of oncocytic subtype have not been well characterized. We analyzed 11 pancreatic ‘oncocytic subtype’ of intraductal papillary mucinous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 79 publications
(94 reference statements)
5
66
0
Order By: Relevance
“…Several other studies have investigated the patterns of mucin protein expression and genetic alterations in IOPNs 10, 14, 37 , including our study analyzing a series of IOPNs by targeted next-generation sequencing 40 , and have shown that IOPNs are genetically distinct from IPMNs. However, to the best of our knowledge, this the first study comparing immunohistochemical profiles of IOPNs and IPMN using a large spectrum of antibodies associated with genetic alterations previously described for DAs and IPMNs as well as antibodies to mucins and differentiation markers.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Several other studies have investigated the patterns of mucin protein expression and genetic alterations in IOPNs 10, 14, 37 , including our study analyzing a series of IOPNs by targeted next-generation sequencing 40 , and have shown that IOPNs are genetically distinct from IPMNs. However, to the best of our knowledge, this the first study comparing immunohistochemical profiles of IOPNs and IPMN using a large spectrum of antibodies associated with genetic alterations previously described for DAs and IPMNs as well as antibodies to mucins and differentiation markers.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, in a recent study investigating eleven IOPNs by targeted next-generation sequencing for a panel of 300 key cancer-associated genes, our group has confirmed that IOPNs are genetically distinct: None of our typical IOPNs revealed KRAS or GNAS mutations and only one had RNF43, PIK3R1 , and PIK3R3 mutations. Instead, ARHGAP26, ASXL1, EPHA8 , and ERBB4 genes were mutated in more than one IOPN 40 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oncocytic variant of IPMN seem to evolve on a completely different pathway. Basturk et al [18] performed high-depth-targeted next-generation sequencing for a panel of 300 key cancer-associated genes on nine typical pancreatic ‘oncocytic subtype’ of IPMN. Interestingly, none of the samples had KRAS or GNAS mutation and only one had RNF43 and PIK3R1 mutations suggesting that the oncocytic subtype is not only morphologically but also genetically distinct.…”
Section: Genetic Makeup Of Ipmnmentioning
confidence: 99%
“…Several commonly mutated genes in IPMNs, including KRAS , GNAS , and RNF43 , are mutated at low frequency or are not mutated in IOPNs [53,76,77,78,79]. Instead, low-frequency of ARHGAP26 , ASXL1 , EPHA8 and ERBB4 mutations have been reported [76].…”
Section: Iopnmentioning
confidence: 99%